Dorado, new variety of pinto beans for the State of Chihuahua - Herrera, Mayra D.; Jiménez-Galindo, José Cruz; Rosales Serna, Rigoberto (Revista Mexicana de Ciencias Agrícolas, 2018)
In Chihuahua, pinto beans are the main commercial class produced by the rainfed-farmers. Currently, high-grain yield pinto beans varieties are required, showing acceptance in the local and national market. The aim was to develop a superior variety of beans than Pinto Saltillo, in earliness, grain size and commercial quality. In the INIFAP-Durango, the variety Dorado (PT08004) was generated, with the genealogic method from the cross between Pinto Mestizo and Pinto Saltillo [(Pinto Mestizo/Pinto Saltillo)-10-6]. This variety showed average yield of 1 554 kg ha-1 and fluctuations between 617 kg ha-1 to 3 706 kg ha-1. On average, Dorado compared to Pinto Saltillo was significantly earlier in maturity (89 vs 97 days) and showed greater weight of 100 seeds (32 g vs 29 g). The growth habit of Dorado is of indeterminate vine, with short non-climbing guides, the average canopy height is 31 cm and the guide grows 89 cm. Dorado grains weigh 32 g/100 seeds and has a range between 26 and 47 g/100 seeds. The grain is transversely elliptical, longitudinally elliptical-cuboid and has a cream-colored seed coat, rich brown paints and the hilum is yellow. Dorado showed tolerance to anthracnose and rust, as well as medium and high values of susceptibility to the common blight and root rot. This variety is in the process of diffusion to determine its potential for adoption, adaptability and potential to increasing the yield and quality of pinto beans produced in Chihuahua.
Keywords: Phaseolus vulgaris L.; quality; market; productivity